(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study explores the functional solutions embedded in traditional houses of Bukhara, Uzbekistan, highlighting how local architectural practices respond to environmental, social, and cultural demands. Traditional Bukhara houses, characterized by inward-oriented layouts, courtyards, and thick adobe walls, offer sustainable solutions suited to arid climates. Despite their historical and cultural significance, modern urban development often overlooks these vernacular strategies, leading to a disconnect between contemporary housing and local climatic needs. The knowledge gap lies in the insufficient integration of these traditional practices into present-day architectural planning. Using a qualitative methodological approach, including field surveys, spatial analysis, and comparative architectural review, this research examines the design logic, spatial organization, and climate adaptability of selected heritage houses in Bukhara. The findings reveal a sophisticated interplay between passive cooling techniques, privacy-driven spatial planning, and multifunctional spaces that support both individual and community life. The results underscore the efficiency of traditional solutions such as the central courtyard’s role in ventilation and thermal regulation, as well as the seasonal use of rooms based on solar orientation. These insights suggest valuable strategies for sustainable architecture in similar climatic zones. The study implies that incorporating traditional knowledge into modern design not only preserves cultural identity but also promotes environmental resilience and functional efficiency in contemporary housing models.